Maternal autoimmune disease and risk of offspring autism spectrum disorder – a nationwide population-based cohort study - Chen, Ching-Chu; Lin, Ching-Heng; Lin, Ming-Chih (Frontiers in Psychiatry, 2023)
Introduction Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders which cause long term social and behavior impairment, and its prevalence is on the rise. Studies about the association between maternal autoimmune diseases and offspring ASD have controversial results. The aim of this study was to investigate whether maternal autoimmune diseases increase the risk of ASD in offspring from a population-based perspective. Methods The data sources were Taiwan’s National Health Insurance Research Database (NHIRD) and Taiwan’s Maternal and Child Health Database (MCHD), which were integrated and used to identify newborns whose mothers were diagnosed with autoimmune disease. Newborns were matched by maternal age, neonatal gender, and date of birth with controls whose mothers were without autoimmune disease using a ratio of 1:4 between 2004 and 2019. Data on diagnoses of autoimmune disease and autism spectrum disorders were retrieved from NHIRD. Patients who had at least 3 outpatient visits or at least 1 admission with a diagnosis of autoimmune disease and autism spectrum disorders were defined as incidence cases. The risks of ASD in offspring were compared between mothers with or without autoimmune disorders. Results We identified 20,865 newborns whose mothers had been diagnosed with autoimmune disease before pregnancy and matched them at a ratio of 1:4 with a total of 83,460 newborn whose mothers were without autoimmune disease, by maternal age, neonatal gender, and date of birth. They were randomly selected as the control group. The cumulative incidence rates of autism spectrum disorders (ASD) were significantly higher among the offspring of mothers with autoimmune diseases. After adjusting for cofactors, the risk of ASD remained significantly higher in children whose mother had autoimmune diseases. Regarding to specific maternal autoimmune disease, Sjögren’s syndrome and rheumatoid arthritis were both associated with elevated risks of ASD in offspring. Conclusion Mother with autoimmune disease might be associated with increasing the risk of autism spectrum disorder in offspring.